Drug utilization of N-Acetylcysteine in COVID-19 inpatients at Santa Elisabeth Hospital, Purwokerto - Heny Ekowati; Faradina Qorina Nadzif; Masita Wulandari Suryoputri (Pharmacy Department, Faculty of Health Sciences, Jenderal Soedirman University, Purwokerto, Indonesia, 2022)
Background: COVID-19 is associated to an oxidant-antioxidant imbalance, which leads to inflammation and tissue damage. N-Acetylcysteine (NAC), in addition to being a mucolytic, has been shown to be an effective antioxidant in the therapy of COVID-19. Objective: The purpose of this study is to evaluate at the NAC usage profile in COVID-19 inpatients at Santa Elisabeth Hospital in Purwokerto. Methods: A descriptive observational design was used to perform the study. Retrospective data were obtained from medical records from July 2020 to July 2021. All patients who met the inclusion criteria were sampled using the total sampling technique. Results: NAC was commonly administered to COVID-19 inpatients who have a mild illness of the disease. The most common symptoms were cough and fever. Patients with mild and moderate severity were given NAC orally (600 mg 3 times a day) and intravenously (5 gram/day), respectively. The duration of NAC administration was in the range of 8-14 days. Conclusion: NAC was one of the therapies used at Santa Elisabeth Hospital Purwokerto for COVID-19 inpatients.